Analisis Penggunaan Metode Garis Lurus Pendekatan Least Square Dalam Memprediksi Jumlah Produksi Produk ARB - Wardhani, Rachmasari Pramita; Siti Norhidayah (Jurnal INOVATOR, 2025)
The company continues to strive to increase production volume in line with customer demand, in this case where sometimes there are obstacles that can hinder the production process so that the resulting product can decrease. Therefore, the company to anticipate a decrease in production volume requires a predictable target by forecasting production that will be produced in the future. This research is expected to use this method to be useful in predicting future production results so that it can later assist company management in determining policies in achieving targets. Data collection techniques are carried out quantitatively using descriptive methods where the implementation is related to data collection and analysis of historical data. Historical data was obtained from ARB product production for 4 years from 2020 to 2023 which was processed using the straight line method with the least square approach and then forecasted again using the same method to predict the amount of production in 2024 and 2025 using the mathematical equation Y = 573,334.93 – 15,359.6X. Analysis from the perspective of the straight line forecasting method with the least square approach can be seen that the decrease in the amount of production is not too significant but further steps are needed to increase the amount of production with other analyses as a stepmaker for company management policies.